ANTICIPATION GUIDE : A STRATEGY OF TEACHING READING COMPREHENSION - Defrioka, Andri (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2013)
This paper reveals an alternative model for teaching reading comprehension at senior high schools. An anticipation guide is a comprehension strategy that is used before reading to activateÂ  students' prior knowledge and build curiosity about a new topic. Before reading, students listen to or read several statements about key concepts presented in the text; they're often structured as a series of statements with which the students can choose to agree or disagree. Anticipation guides stimulate students' interest in a topic and set a purpose for reading.